2019
DOI: 10.1017/s0952523819000087
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin and calbindin immunoreactivity in the inner retina of humans and marmosets

Abstract: In primate retina, the calcium-binding protein calbindin is expressed by a variety of neurons including cones, bipolar cells, and amacrine cells but it is not known which type(s) of cell express calbindin in the ganglion cell layer. The present study aimed to identify calbindin-positive cell type(s) in the amacrine and ganglion cell layer of human and marmoset retina using immunohistochemical markers for ganglion cells (RBPMS and melanopsin) and cholinergic amacrine (ChAT) cells. Intracellular injections follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 68 publications
5
16
0
Order By: Relevance
“…We also compared the densities of the two most intense ChAT + cell populations in the INL (putative OFF starburst cells) and GCL (putative ON starburst cells) and found that the density of ON starburst cells was on average slightly lower than that of OFF starburst cells (marmoset: 655 vs. 685 cells/mm 2 , buzzard: 2500 vs. 3250 cells/mm 2 , from areas of 2–10 mm in marmoset and 8–24 mm in buzzard). This is in line with the density of ON and OFF ChAT cells in mouse retina (945 vs. 1100 cells/mm 2 , Jeon et al, 1998) but differs from that in human and macaque retina where ON ChAT cells are more frequent than OFF ChAT cells (ratio of 70:30; Chandra et al, 2019; Rodieck & Marshak, 1992). The reported ON to OFF ratio of 30:70 in marmoset (Chandra et al, 2019; Moritoh et al, 2013; Weltzien et al, 2015) can be explained with the additional ChAT + /Sox2 − cells in the INL.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We also compared the densities of the two most intense ChAT + cell populations in the INL (putative OFF starburst cells) and GCL (putative ON starburst cells) and found that the density of ON starburst cells was on average slightly lower than that of OFF starburst cells (marmoset: 655 vs. 685 cells/mm 2 , buzzard: 2500 vs. 3250 cells/mm 2 , from areas of 2–10 mm in marmoset and 8–24 mm in buzzard). This is in line with the density of ON and OFF ChAT cells in mouse retina (945 vs. 1100 cells/mm 2 , Jeon et al, 1998) but differs from that in human and macaque retina where ON ChAT cells are more frequent than OFF ChAT cells (ratio of 70:30; Chandra et al, 2019; Rodieck & Marshak, 1992). The reported ON to OFF ratio of 30:70 in marmoset (Chandra et al, 2019; Moritoh et al, 2013; Weltzien et al, 2015) can be explained with the additional ChAT + /Sox2 − cells in the INL.…”
Section: Discussionsupporting
confidence: 65%
“…This is in line with the density of ON and OFF ChAT cells in mouse retina (945 vs. 1100 cells/mm 2 , Jeon et al, 1998) but differs from that in human and macaque retina where ON ChAT cells are more frequent than OFF ChAT cells (ratio of 70:30; Chandra et al, 2019; Rodieck & Marshak, 1992). The reported ON to OFF ratio of 30:70 in marmoset (Chandra et al, 2019; Moritoh et al, 2013; Weltzien et al, 2015) can be explained with the additional ChAT + /Sox2 − cells in the INL.…”
Section: Discussionsupporting
confidence: 65%
“…The gigantic displaced M1 ganglion cells of human retina are a distinct type based on their morphology 5,22 , and the data reported here on the preponderance of excitatory synaptic inputs from OFF bipolar cells to their homologs in macaque retina support this nding. This is the rst study to identify the types of bipolar cells that provide input to displaced ipRGCs using electron microscopy (EM).…”
Section: Discussionsupporting
confidence: 76%
“…Labeling for the photoreceptor terminal marker SV2 at D120 (red) demonstrated that structures consistent in shape with photoreceptor terminals (white arrows) were detected in both dissection ( Figure 4 E) and suspension-grown ( Figure 4 F) cultures. We co-labeled with the calcium binding protein calbindin (green, Figure 4 E,F) which is expressed in the human retina in cones, subsets of inner retinal neurons, and some ganglion cells [ 34 , 35 ], and observed calbindin positive cells (yellow arrows, Figure 4 E,F) under both culture conditions. However, cells exhibiting horizontal cell morphology, characterized by large squat cell bodies and processes that penetrated horizontally through the tissue (i.e., perpendicular to the length of the photoreceptor) were detected only in dissection grown cultures.…”
Section: Resultsmentioning
confidence: 99%